PENINGKATAN KUALITAS PELAYANAN MENGGUNAKAN METODE SERVQUAL DAN KANO - Wulan Purnamasari; Rizki Bachtiar Yuliansyah (Jurnal Ilmu Sosial dan Humaniora, 2020)
Customer satisfaction is one of the determinants of the survival of a company. Service quality is an important factor for companies, especially for companies engaged in services. Service quality has a close relationship with customer satisfaction. Satisfaction will be felt maximally by the customer, if the customer gets more than his expectations. Satisfied customers, they will give a positive response. This study aims to broadly improve the quality of Indonesian DigIs services, in the hope that consumers' desires and needs can be achieved and in line with their expectations of management perceptions. The use of Servqual and Kano methods is expected to later identify the GAP between customer needs and needs that must be improved and the technical response that must be carried out by management, so that customer satisfaction is expected to increase the quality of Indonesian DigIs services so that the company can grow rapidly.This research began with interviews and distributing questionnaires to 50 consumer respondents when getting responses about Indonesian DigIs services used to test validity and reliability. Service attributes consist of 30 items using the Servqual method consisting of 5 dimensions, namely tangibles, reliability, empathy, assurance, and responsiveness. After distributing questionnaires, the next step is to do data processing with GAP calculations to determine customer satisfaction with the quality attributes of Indonesian DigIs services. Then processed using Kano method.Priority attributes to be repaired and improved by Indonesian DigIs companies to be in accordance with the wishes and needs of customers based on VoC (Voice of Customer) through Servqual and Kano methods is the first priority in the tangible dimension is the neat appearance of employees who need to be improved again, if necessary uniformed ( wearing dresscode). The first priority in the reability dimension is the security of the system that is operated to be further enhanced by maintaining the confidentiality of the consumer database and security in operation. The first priority in the dimensions of responsiveness, is the speed of officers in providing services should management provide training in both soft skills and hard skills that can support the speed of employees in providing services. The main priority in the assurance dimension, namely the officer has the knowledge and ability to provide information, in this case the management should provide additional training that can support the knowledge of the service officers. While the main priority on empathy dimensions, is about providing information and instructions on how to operate the system clearly, the management should conduct an SOP evaluation, so that the operation of the system can run better. The proposal to improve Indonesian DigIs services according to customer desires and needs based on VoC (Voice of Customer) using Servqual and Canoeing methods is the improvement or evaluation of SOPs, reviewing facilities and infrastructure (focused on room facilities) and providing additional training to support HR performance.